Influence of additive on the aggregation behavior of drug and cationic hydrotrope aniline hydrochloride mixtures: a physicochemical assessment. (28th August 2020) - Alghamdi, Yousef G.; Rub, Malik Abdul; Azum, Naved; Asiri, Abdullah M.
Abstract: We investigated the influence of an additive (50 mmol kg –1 NaCl/300 mmol kg –1 urea [U]) on the aggregation of amphiphilic promethazine hydrochloride (PMH) drug and cationic hydrotrope–aniline hydrochloride (AnHCl) mixtures at various temperatures and ratios. The drug PMH is mostly used for the treatment of allergic symptoms. The obtained critical micelle concentration ( cmc ) values are well below the cmc id (ideal cmc ) value, which confirms interactions between components PMH and AnHCl in the solution mixture. The micellar mole fraction ( X 1 Rub, X 1 Rod, and X 1 id ) of the first component (AnHCl) was evaluated using different models, which suggested greater involvement of AnHCl in mixed micelles (as expected); besides, the obtained micellar mole fraction values increase with increase in the mole fraction ( α 1 ) of AnHCl. The interaction parameter ( β ) values obtained were negative, which confirms attractive interaction or synergism among the components. Activity coefficients ( f 1 Rub [AnHCl] and f 2 Rub [PMH]) values are always found below one confirming the nonideality as well as attractive interaction between the components. Different physicochemical parameters evaluated suggested attractive interaction between the components (PMH and AnHCl) in all studied solvents; however, in salt media, the interaction increases to some extent, whereas in urea media, it decreases to some extent. Diverse thermodynamic parameters (Gibbs free energy [Δ G m 0 ], enthalpy [Δ H m 0 ], and entropy [Δ S m 0 ]) of micellization were computed and discussed separately. The excess free energy ( ∆ G ex Rub ) values of all systems were negative, suggesting higher stability of formed mixed micelles as compared with singular‐component micelles. Abstract : Herein, we investigated the influence of an additive on the aggregation of promethazine hydrochloride (PMH) drug and aniline hydrochloride (AnHCl) mixtures at various temperatures. The interaction parameter ( β ) values obtained were negative, which confirms attractive interaction among the components. Different physicochemical parameters evaluated suggested attractive interaction between the components (PMH and AnHCl) in all studied solvents; however, in salt media, the interaction increases, whereas in urea media, it decreases. Diverse thermodynamic parameters of micellization were computed and discussed separately.